HUBUNGAN KADAR LIPID DARAH DENGAN DERAJAT KEPARAHAN NEUROPATI DIABETIK PERIFER DI RUMAH SAKIT WAHIDIN SUDIROHUSODO - Devina Irawan,* Audry Devisanty Wuysang,* Yudy Goysal* (NEURONA, 2019)
INTRODUCTION BLOOD LIPID LEVELS PLAY A ROLE IN THE ETIOPATHOGENESIS OF DIABETIC NEUROPATHY AND HAVE A SIGNIFICANTRELATIONSHIP TO THE SEVERITY OF DIABETIC NEUROPATHY IN PATIENTS WITH DIABETES MELLITUS DM